Assessment of soil properties and trace element accumulation in arid regions: A case study of Kalmykia's central dry steppe zone, Russia - Raisa Mukabenova; Saglara Mandzhieva; Vishnu D. Rajput; Aleksey Buluktaev; Inna Zamulina; Altana Adyanova; Nikita Dzhimbeev; Vasiliy Sayanov; Sudhir S. Shende; Anatoly Barakhov; Svetlana Sushkova (Eurasian Journal of Soil Science, 2024)
Soil plays a pivotal role in ecosystem health and agricultural productivity. This study focuses on a critical region for soil research, Kalmykia's central dry steppe zone in southern Russia, characterized by arid conditions and unique challenges. Our investigation aimed to evaluate the current state of soil properties and assess trace element accumulation within this environment. The region's distinctive characteristics, including being home to Europe's first desert, present a complex scenario for soil conservation and management. A thorough analysis of key physicochemical properties, including organic matter content, soil texture, pH levels, and the concentrations of trace elements (V, Cr, Co, Ni, Cu, Zn, Sr, and Pb) using established methodologies, was conducted. Our findings revealed several crucial insights into the soil conditions of this arid region. Soil samples predominantly consisted of Haplic Kastanozems Sodic, characterized by low organic carbon content (0.3-1.9%). Soil texture analysis indicated a predominantly light and medium loamy granulometric composition with a prevalence of sandy fractions. Soil pH values ranged from neutral (pH = 7.6-7.9) to slightly alkaline (pH = 8.0-8.4). Furthermore, the study provided the first assessment of soil conditions in residential areas of the Caspian Lowland's arid region. Notably, trace element analysis showed elevated concentrations of several metals, with Sr having the highest levels. Co, Cr, and Zn concentrations did not significantly increase compared to the background values. The results of this soil fertility evaluation hold significance for soil restoration and conservation efforts in this unique and fragile ecosystem. In conclusion, this study underscores the urgent need for soil monitoring and management practices to address soil degradation and desertification driven by overgrazing and erosion. Understanding the physicochemical properties and trace element dynamics in arid regions is essential for developing strategies to restore and conserve these valuable soils.